Ocean acidification and food availability impacts on the metabolism and grazing in a cosmopolitan herbivorous protist Oxyrrhis marina - Wang, Na; Gao, Kunshan (Frontiers in Marine Science, 2024)
The heterotrophic dinoflagellate Oxyrrhis marina is an essential microzooplankton in coastal waters, linking the energy transfer from phytoplankton to higher trophic levels. It is of general significance to investigate how it responds and acclimates to ocean acidification (OA), especially under varied availabilities of food. Here, O. marina was exposed and acclimated to three pCO2 levels (LC: 415, MC:1000, HC:1500 μatm) for 60 days, and then was further grown under the CO2 levels with different levels of food (the microalgae Dunaliella salina) availability for about 8 generations. The OA treatments did not significantly hamper its growth and ingestion rates even under the reduced food availability and starvation (deprived of the microalgae), which significantly reduced its growth rate. While the impacts of OA on the growth and ingestion rates of O. marina were insignificant, the OA treatments appeared to have resulted in a faster decline of the heterotrophic dinoflagellate cells during the starvation period. Nevertheless, the acidic stress under the elevated pCO2 of 1000 or 1500 μatm decreased its respiration by about 53% or 59% with the high and by about 26% or 23% with the low food availability, respectively. Such OA-repressed respiration was also significant during the starvation period. On the other hand, the OA treatments and deprivation of the microalgae synergistically reduced the cellular quota of particulate organic C, N and P, resulting in a reduction of food value of the heterotrophic dinoflagellate as prey. In conclusion, our results show that O. marina is highly resilient to future ocean acidification by reducing its respiration and sustaining its ingestion of microalgae.